(untitled) (Multidisciplinary Journal of Science and Technology, 2026)
This paper investigates the mechanisms responsible for the formation of micro-pitting and scuffing in gear transmissions, as well as their influence on lubrication processes. Friction and temperature rise generated during gear operation lead to a reduction in lubricant film thickness, resulting in localized damage on contacting surfaces. In this study, gear tooth surfaces affected by micro-pitting are treated as topographic surfaces, and the motion of a thin lubricant film over these surfaces is mathematically modeled. The modeling approach is based on the lubrication approximation of the Navier–Stokes equations for an incompressible Newtonian fluid. In addition, the hydrodynamic behavior of a thin liquid film flowing over topographic irregularities on an inclined surface is analyzed. The obtained results provide a scientific basis for improving lubrication performance, reducing friction and wear, and enhancing the reliability and service life of gear transmissions used in electric vehicles, wind turbines, and other mechanical systems.